Traditional Chinese medicine Xiaosheng Powder for dry eye disease: A protocol for systematic review and meta analysis. Issue 35 (28th August 2020) - Xu, Jing; Chen, Shuntai; Hao, Xiaofeng; Wu, Gaiping; Wang, Shihui; Yuan, Hang; Jin, Qi; Sun, Mei; Xie, Like
Abstract: Background: Dry eye disease (DED) has shown a significant increase in recent years, which seriously affects people's work and life. Xiaosheng Powder, a traditional Chinese medicine decoction, has been widely used in treating DED. However, there is no systematic review of the results of the study on this therapeutic effect. The purpose of this review is to evaluate the effectiveness and safety of Xiaosheng Powder in the treatment of DED. Methods and Analysis: The electronic databases to be searched will include MEDLINE (PubMed), Cochrane Central Register of Controlled Trials in the Cochrane Library, Excerpta Medica Database, China National Knowledge Infrastructure, China Scientific Journal Database, Wanfang Database and Chinese Biomedical Literature Database. Papers in English or Chinese published from inception to 2020 will be included without any restrictions. Improvement in Ocular Surface Disease Index will be assessed as the primary outcomes. Tear break-up time, Schirmer I test, fluorescent, adverse events, and the recurrence rate after at least 3 months of the treatment will be evaluated as secondary outcomes. We will conduct a meta-analysis of randomized controlled trial if possible. The methodological qualities, including the risk of bias, will be evaluated using the Cochrane risk of bias assessment tool, while confidence in the cumulative evidence will be evaluated using the Grading of Recommendations Assessment, Development, and Evaluation approach. Ethics and Dissemination: It is not necessary for a formal ethical approval because the data is not individualized. The results of this review will offer implications for the use of Xiaosheng Powder as a treatment for DED. This knowledge will inform recommendations by ophthalmologist and researchers who are interested in the treatment of DED. The findings of this systematic review will be disseminated through peer-reviewed publications and conference presentations. Trail registration number: PROSPERO CRD42020147709.